Making Chimerica great again. (21st December 2018) - Ferguson, Niall; Xu, Xiang
Abstract: A decade after the outbreak of the global financial crisis, a large trade imbalance between the world's two biggest economies, the U.S. and China, still exists and is more politically contentious than ever. This economic relationship, which we termed 'Chimerica' in 2007, seemed likely to end as a result of the global financial crisis. Yet this did not happen. In this paper, we examine the evolution of Chimerica in the aftermath of the global financial crisis and explain how the stimulus policies of both the U.S. and China have contributed to its survival. We show how stimulus policies helped change Chimerica from a marriage of opposites to a marriage of equals. We then explain why this marriage is now destined for strife, in the form of a trade war between the U.S. and China. The consequences of such a trade war would deeply impact the global economy. We believe constructive negotiations on trade rebalancing and policy coordination are therefore needed to avoid a disruptive end to Chimerica.